PERDEBATAN PELAKSANAAN PUTUSAN PENENTUAN HASIL AKHIR SENGKETA TANAH DI KALIMANTAN YANG DI JADIKAN SEBAGAI IBU KOTA NEGARA INDONESIA GEOPOLITIK DI INDONESIA - Firman, A Masse; Saravistha, Deli Bunga (Universitas Mahendradatta Denpasar, 2024)
A dispute is a difference of interest between individuals or institutions on the same object that is manifested in the relationships between them. On August 26, 2019, President Joko Widodo announced the transfer of the country's capital (IKN) to East Kalimantan Province. To begin with, the National Development Planning Agency (Bappenas) has investigated various aspects related to the stage of ICT transfer. These include the economic impact, regional readiness, and the potential development of industrial areas. In the preventive protection of the law, the government should take into account the fate of the local citizens when making plans for the development of the ICT area, both in making decisions and decisions related to the construction of the Nusantara ICT. Following the decision to transfer the capital of Nusantara to the East Kalimantan Province, the transfer of land rights has increased, according to data from the Regional Office of the National Agriculture Authority of the East Calimantan province. By 2020, the rights to land were transferred through a sale agreement at 175 locations in the territory of the capital of Nusantara. By 2021, the number of transactions has increased significantly to 294. Based on these backgrounds, researchers are interested in conducting research entitled “Debate on the Implementation of the Final Decision of the Land Dispute in Kalimantan which is to be made the capital of Indonesia”, through two issues to be discussed, namely, First, the setting up of land freezing as part of the ICT program in East Kalimanthan and Second, on the social impact of the land-freezing program on citizens in particular in East Calimantan. The research method in this research uses normative law research.